Predictive Value of In Vitro Adenosine Triphosphate-Based Chemotherapy Response Assay in Advanced Gastric Cancer Patients Who Received Oral 5-Fluorouracil after Curative Resection - Lee, Ji Hyun (Korean Cancer Association, 2011)
PURPOSE: To assess the usefulness of adenosine triphosphate-based chemotherapy response assay (ATP-CRA) results in advanced gastric cancer patients receiving adjuvant chemotherapy. MATERIALS AND METHODS: Sixty-two patients underwent curative surgical resection between January, 2006 and December, 2008. Their highly purified surgical specimens were evaluated by ATP-CRAs. Of the 62, 49 had successful assay results and they received either oral 5-fluorouracil or other chemotherapies. We retrospectively analyzed data for 24 patients who were treated with oral 5-fluorouracil and whose assays were successful. RESULTS: The median observation time was 24.6 months (range, 10.1 to 40.9 months). The median treatment time was 11.2 months (range, 1.2 to 17.7 months). The median age was 66 years (range, 30 to 81 years). Patients were grouped into sensitive- and resistant-groups according to adenosine triphosphate-based chemotherapy response results for fluorouracil. The sensitive-group showed a significantly longer time to relapse (not reached in the sensitive-group vs. 24.8 months in the resistant-group, p=0.043) and longer overall survival compared to the resistant-group (not reached in the sensitive-group vs. 35.7 months in the resistant-group, p=0.16, statistically insignificant). CONCLUSION: Patients who receive curative surgical resection significantly benefit from sensitive adjuvant chemotherapy according to ATP-CRA results for time to relapse.